Counterfactual protocol within device independent framework and its insecurity - Kamaruddin, Suhaili; Shamsul Shaari, Jesni; Kolenderski, Piotr (Springer Nature, 2020)
We consider the counterfactual protocol proposed in Phys. Rev. Lett., 103, 230501 (2009) within a device independent framework and show how its security can easily be compromised. Capitalising on the fact that the protocol is based on the use of a single photon entanglement phenomenon, we propose an equivalent protocol. It can be made secure within such a pessimistic framework against a supra-quantum Eve limited only by the no-signalling principle. The equivalence the protocol demonstrates the possibility of device independent framework for counterfactual quantum cryptography.